Analysis of the current state and development trends of the banking deposit services market in Kazakhstan - Sukhanberdina, B.B.; Kurmanova , G.K. (BUKETOV BUSINESS REVIEW, 2019)
The article is devoted to the study of the Kazakhstan market of Bank Deposit services. The study is aimed at solving the practical problem and makes a certain contribution to the stable functioning of the Deposit services market and the banking system of the country as a whole. The results of the study showed that the market of banking services covered about 50–60 % of the population; political and economic stability, expressed in controlled macroeconomic indicators, gives the Deposit market a positive dynamics; against the background of a significant devaluation of the tenge, the growth rate of deposits of individuals in recent years has decreased; in conditions of almost identical interest rates, commercial banks tend to actively use non-price instruments; increased competition between commercial banks for customers contributes to the development of new additional banking services. It is established that commercial banks are currently actively using various marketing approaches to the organization of retail business. It was also revealed that the preferences and expectations of Bank customers have changed. The reliability of the Bank comes to the fore, the second — the level and quality of service, and only in the third plan—profitability. Therefore, modern banks need to pay more attention to the level and quality of service. It is proved that in modern conditions of development of the market of Bank Deposit services it is necessary to strengthen the strategic and organizational role of Bank marketing. All this should be done on the basis of expanding the use of new banking information technologies.